Planar cell polarity signaling in collective cell movements during morphogenesis and disease. - Muñoz-Soriano, V.; Belacortu, Y.; Paricio, N. (Current Genomics, 2012)
Collective and directed cell movements are crucial for diverse developmental processes in the animal kingdom, but they are also involved in wound repair and disease. During these processes groups of cells are oriented within the tissue plane, which is referred to as planar cell polarity (PCP). This requires a tight regulation that is in part conducted by the PCP pathway. Although this pathway was initially characterized in flies, subsequent studies in vertebrates revealed a set of conserved core factors but also effector molecules and signal modulators, which build the fundamental PCP machinery. The PCP pathway in Drosophila regulates several developmental processes involving collective cell movements such as border cell migration during oogenesis, ommatidial rotation during eye development, and embryonic dorsal closure. During vertebrate embryogenesis, PCP signaling also controls collective and directed cell movements including convergent extension during gastrulation, neural tube closure, neural crest cell migration, or heart morphogenesis. Similarly, PCP signaling is linked to processes such as wound repair, and cancer invasion and metastasis in adults. As a consequence, disruption of PCP signaling leads to pathological conditions. In this review, we will summarize recent findings about the role of PCP signaling in collective cell movements in flies and vertebrates. In addition, we will focus on how studies in Drosophila have been relevant to our understanding of the PCP molecular machinery and will describe several developmental defects and human disorders in which PCP signaling is compromised. Therefore, new discoveries about the contribution of this pathway to collective cell movements could provide new potential diagnostic and therapeutic targets for these disorders.